Efforts to Increase Cyber Crime Awareness through Counseling for Student Organizations at Nahdlatul Ulama University of Cirebon - Asep Hermawan; Agustiana A; Amir Machmud (Yayasan Daarul Huda Kruengmane, 2025)
The rapid development of information technology has brought various conveniences to daily life; however, it has also led to an increasing potential for cybercrime. Students, as active users of digital technology, are among the groups most vulnerable to various forms of cybercrime. This community service activity aims to enhance the awareness and understanding of student organizations regarding cybercrime and its preventive measures. The methods used include counseling, interactive discussions, and case simulations. The results of the activity show an improvement in participants’ understanding of the types of cybercrime, their impacts, and the preventive steps that can be taken. Thus, this activity is expected to foster more responsible and secure digital behavior among students.